Climate change as an environmental threat on the central plains of the Carpathian Basin based on regional water balances - Tran, Hop Quang; Fehér, Zsolt Zoltán; Túri, Norbert; Rakonczai, János (Geographica Pannonica, 2022)
Climate change is an essential environmental challenge nowadays. Its effects are already being felt in multiple ways. In the future, we will also have to adapt to its effects because of our farming and our daily lives. In our research, we assessed the climate sensitivity of the lowland areas of Hungary through the changes in landscapes and the changes in groundwater resources that have the greatest impact on agriculture, using data from more than half of a century. We have quantified that at the mid-territory level (5-10 thousand km2) the groundwater resources show up to 3-5 km3/year changes in both positive and negative directions due to climatic effects. This significantly exceeds the anthropogenic water uses (the total water use of Hungary is about 5 km3 per year), so the effect of climate is the determining factor in the changes of regional water resources. Future changes in water circulation were modelled using the MIKE-SHE model in two micro-regions in Hungary. We have found that already at the level of the small catchments presented in our study, the water shortage increases by hundreds of millions of m3 per year due to the expected increase in temperature (mainly due to the increase in evapotranspiration), which cannot be compensated by current water supply solutions. Model simulations have confirmed previous results showing that groundwater movements play a very important role even in lowland landscapes. Based on our research, we would like to draw the attention of decision-makers and agricultural experts to the fact that current methods (irrigation, regional water transfers) are not sufficient for successful adaptation to climate change. So, it is not the limited precipitation but the inappropriate agricultural practices that cause a real threat in a changing climate. Based on our research, we have made a proposal for the adaptation of agriculture to climate change.